2014
DOI: 10.18287/0134-2452-2014-38-3-372-376
|View full text |Cite
|
Sign up to set email alerts
|

Spatial integration of optical beams using phase-shifted bragg grating

Abstract: Пространственное интегрирование оптических пучков с использованием многослойных… Головастиков Н.В., Быков Д.А., Досколович Л.Л. 372Компьютерная оптика, 2014, том 38, №3 Аннотация Рассмотрена дифракция двумерного оптического пучка на многослойной брэгговской структуре. Показано, что брэгговская решётка с дефектом позволяет выполнить операцию пространственного интегрирования двумерного профиля падающего пучка с центральной пространственной частотой, близкой к константе распространения квазиволноводной моды дефек… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
“…Even The scope of research topics covered by the journal has been extended during 10 years of its publication, now embracing new areas such as plasmonics and diffractive nanophotonics [31][32][33][34][35][36][37][38][39][40][41][42][43], geo-information technologies [44][45][46][47], systems of technical vision [48][49][50][51][52], interpretation and understanding of nanoscale objects images [53][54][55][56], intellectual analysis of video streams [57][58], optical computations [59][60][61], analysis of hyperspectral data [62][63][64], development of hyperspectrometers for Earth remote sensing [65][66][67][68], new types of laser beams with unique properties [69][70][71], sharp focusing [72][73][74], new types of lighting devices [75][76]. Furthe...…”
Section: Journalmentioning
confidence: 99%
“…Optical devices implementing required temporal and spatial transformations of optical signals are of great interest for a wide range of practical applications including alloptical information processing and analog optical computing [1].Various resonant structures are known to implement these operations including phase-shifted Bragg gratings (PSBG). PSBGs have been used both for temporal differentiation and integration of an optical pulse envelope [2][3][4] and for spatial differentiation and integration of a monochromatic optical beam profile [5,6]. The utilization of resonant structures is attributable to the fact that their reflection (transmission) coefficient of the structure in the vicinity of the resonance can be described by the Fano profile, which in turn can approximate the transfer function of a differentiating or integrating filter.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous works, temporal and spatial transformations of the incident pulse envelope were considered separately. Temporal transformations in [2][3][4] were investigated without taking into account the spatial configuration of the incident optical pulse, whereas spatial operations in [5,6] were studied in the case of a monochromatic incident beam. In this regard, the description of spatiotemporal transformations of optical pulses implemented by PSBG in the general 3D case is of great interest.…”
Section: Introductionmentioning
confidence: 99%